2014
DOI: 10.1080/12538078.2013.871209
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the flora of Asian and European countries: new national and regional vascular plant records

Abstract: The paper presents new records for 39 vascular plant species from eight Eurasian countries. Aniselytron treutleri (Poaceae), Hackelochloa granularis (Poaceae), Melica kozlovii (Poaceae) and Melica nutans (Poaceae) are reported from China; Dichondra micrantha (Convolvulaceae) from Hungary; Orobanche serbica (Orobanchaceae) and Viscum album subsp. austriacum (Santalaceae) from Italy; Petrorhagia prolifera (Caryophyllaceae), Puccinellia schischkinii and Stipa pulcherrima (Poaceae) from Kyrgyzstan; Megadenia spelu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…2, 3, 4, 5, 6), these two taxa differ also in their geographical distribution. The former is a more south-westerly, Central Asian taxon, occurring mainly in Kazakhstan, Kyrgyzstan, Uzbekistan, and Tajikistan (Lavrenenko and Nikolskaya 1965; Nobis et al 2014c), whereas S. macroglossa subsp. kazachstanica is a more north-easterly, Central Asian taxon, occurring mainly in western Mongolia, western China, eastern Kazakhstan and eastern Kyrgyzstan (Nobis et al 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…2, 3, 4, 5, 6), these two taxa differ also in their geographical distribution. The former is a more south-westerly, Central Asian taxon, occurring mainly in Kazakhstan, Kyrgyzstan, Uzbekistan, and Tajikistan (Lavrenenko and Nikolskaya 1965; Nobis et al 2014c), whereas S. macroglossa subsp. kazachstanica is a more north-easterly, Central Asian taxon, occurring mainly in western Mongolia, western China, eastern Kazakhstan and eastern Kyrgyzstan (Nobis et al 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…ru). However, herbarium materials at LE from the Crimea (Mys Fiolent) include individuals of O. ritro, parasitizing Echinops ritro [20], with a characteristic creamy or less common yellow color of corolla [27,62]. Many species of the genus Orobanche, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in central and northern parts of Europe the genera comprise about 30 species (17 established and 2 ephemerophytes from Poland), which are mostly rare, endangered or declining [e.g. 2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These parasitic genera consist of plants, which possess very reduced vegetative organs and are highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Its vascular plant flora is relatively species-rich, including around 4550 taxa [4]. Results of recent studies have shown that this number is not final, as some taxa new to the Tajik flora have been reported [5][6][7][8][9]. Approximately 30% of vascular plant species known from Tajikistan are generally accepted as endemics [4].…”
Section: Introductionmentioning
confidence: 98%